Implementation of Family Functions in Early Marriage Couples in Padang City - Maihasni, Maihasni; Anggraini, Nini; Fachrina, Fachrina (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
The family has a very important role in preparing quality Indonesian human resources. The function of the family that is carried out can make a significant contribution to the development of its members.Â  Families that can carry out family functions well have the ability to meet the basic needs of family members in facing challenges and making adjustments to changes in themselves and their environment.For family functions to run well, certain conditions must be met such as age, marital status, employment status, level of education, knowledge of family functions, and access to information. This condition is not met for early marriage couples. This research aims to: (1). Identify family functions that can be carried out by couples married at an early age. (2) Analyze the obstacles faced by couples married early in carrying out family functions.This research was conducted in Padang City with a qualitative approach with a descriptive type. Data collection uses in-depth interviews and observations. Informants were determined using snowball sampling. Data was analyzed qualitatively and interpretatively.Â  The research was conducted on five informants and varying levels of education. As for the family functions that can be carried out by early married couples, almost all of them can be carried out, such as; religious function, affection function, reproductive function, education and socialization function, economic function, recreation function, protection function, and environmental development function, although in limited cases. Meanwhile, the obstacles faced by early married couples in carrying out family functions, such as lack of financial independence, and interaction problems.